Assessment of community disaster resilience among Kelantan flood affected community: A cross sectional study. - Ludin, Salizar Mohamed; Maalek, Muhammad Afdhaluudin; Firdaus, Mohd Khairul Zulhasyimi; Arbon, Paul (IIUM Medical Journal Malaysia, 2016)
Introduction: Community disaster resilience (CDR) is the community abilities to cope, with stands and accommodate disturbances caused by hazard exposure. In 2014, the east coast Malaysia had the worst flood disaster and many lost their home, belongings and everything was uncontrolled and messy. Despite the regular flood, the status of CDR is unknown. Thus, the aim of this study is to assess the Kelantan’s flood victims on their CDR level, resilience factors and its association to demographic profiles. Methods: A crosssectional survey using CCRAM28 questionnaire was done in 6 areas within 6 months in 2015. Respondents recruited purposely as they meet the criteria (18 years and above, understand Malay, moved to flood shelter). Descriptive and inferential analyses were done using SPSS software. Results: 100% returns rate (n=386). CDR level (mean) were between medium (2.34- 3.66) and high (3.67- 5.00). Among the living area, marital status, age, gender, income, religion, education, only gender (p = 0.003) and education level (p = 0.001) were significantly related to CDR level. Positive and strong correlation were seen between each resilience factors namely leadership (p = 0.001), collective efficacy (p = 0.001); preparedness (p = 0.001); place attachment (p = 0.001) and social trust (p = 0.001) consecutively. Conclusions: The study shows an acceptable CDR level, strong association between each of the resilience factors and between communities’ demographic characteristics and their CDR level. To ensure high level and continuous CDR, assessment and activities to build the resilience should be introduced by the state of Kelantan or the government of Malaysia.